STUDI POTENSI PRODUKSI OKSIGEN HUTAN KOTA DI KAMPUS UNIVERSITAS INDONESIA, DEPOK - E. Irwan Afrizal; Indung Siti Fatimah; Bambang Sulistyantara (Jurnal Lanskap Indonesia, 2010)
Problems faced by urban area progressively becomingcomplex that can be seen from the growing of built area in town and the decreasing of green space area. The aim of this study is to evaluate influence of urban forestat University of Indonesia Depok as green space area to supply O2and also factors influencing the availibility of O2. Research executed at urban forest University of Indonesia Campus in Depok, South Jakarta. Method which is used in this study is survey method using oxygen requirement approach by Gerarkis. Estimation of student and resident amount also oxygen requirement can be calculated using trend linear analysis method and Doubled Interest Formula. Internal factors of the system are the amount of motor vehicle and residents. This research has given result that UI urban forest’s ability in supplying O2required by motor vehicle has been degraded. Whileits ability to supply O2for residents has been increased.